DEVELOPMENT OF NEW METHODS FOR ANALYTICAL ESTIMATION OF SELF-OSCILLATION STABILITY IN RELAY CIRCUITS - A. G. Deripaska; M. V. Soklakova; E. P. Chernyshev (Известия высших учебных заведений России: Радиоэлектроника, 2018)
This article is devoted to the  development of analytically  described self-oscillation  stability  research  technique.  The case when  the  linear part  of the  system contains transfer function with a zero pole is considered. Typically the transfer function study,  where  the  numerator degree  is two orders  of magnitude less than  the  denominator degree  is creates no problems. However, the presence of a zero pole makes the case special and requires  investigation.A comparative evaluation of the results of self-oscillation analytical  calculation  and stability analysis is given, by means of technique developed for symmetric self-oscillations with half-period repetitions and asymmetric ones with period repetitions.The presented technique is a significantly  new scientific step  in the development of methods for calculating  non-linear systems. It also allows  us to evaluate the  accuracy  of approximate calculation methods, which  is important for precision systems. The technique is relatively  easy  to  implement. It allows  to  find  a solution  as well as for the  cases  having  been unanalyzable so far.